Leveraging Multimodal Literacies: Design of a Multimodal Research Journal - McKee, Lori (Journal of the Canadian Association for Curriculum Studies, 2020)
This presentation explores the interplay between the researcher’s understandings of multimodal literacies (Walsh, 2011) and the design of a digital, multimodal, research journal using the Google Keep application (Google, 2018). The examples come from a year-long action research study (Pine, 2009) designed to inform the pedagogies of a novice educator. The research journal design was built upon understandings of multimodal literacy that recognize that meanings can be shaped through the researcher-digital interface (Kuby & Rowsell, 2017), and it was extended from uses of Google Keep for pedagogical documentation in kindergarten classrooms (Vaillancourt, 2017). The presentation highlights the ways that the researcher created the journal using text and publicly useable images and analyzed the data through hashtag labels. Through this discussion, the researcher considers the ways meaning was shaped through the affordances and constraints of the journal. The presentation contributes to knowledge related to the ways that multimodal literacy, and digital tools designed for teaching practice, can be used within research designs.